Utilization of Liquid Emulsion Membranes To Set Aside Nickel Ions In Liquid Waste - Bambang Ismuyanto (Natural B, Journal of Health and Environmental Sciences, 2012)
Emulsion liquid membrane containing Di-(2ethylhexyl) phosphoric acid (D2EHPA) have been applied to remove nickel ion from wastewater of electroplating industry. Membrane was made from 0.1 mL of Span – 80; 0.6 mL of D2EHPA and 9.3 mL kerosene. Internal phase was made from 5 mL HCl 0,1 N, while the external phase that was nickel solution varied on concentration for 100-300 ppm. The separation process was done by stirring the solution in various rate of 100-250 rpm at 4 minutes. The last concentration of nickel was measured by using visible spectrophotometry at wavelength 470 nm by dimethylglyoxime method. From the experimental results, it has been established that increasing in stirring rate could increasing permeated nickel ion value. While increased on concentration of external phase also promoted permeated nickel ion value, with highest value 75%.